2015
DOI: 10.1016/j.ic.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic single exponential time algorithms for connectivity problems parameterized by treewidth

Abstract: Abstract.It is well known that many local graph problems, like Vertex Cover and Dominating Set, can be solved in 2 O(tw) n O(1) time for graphs with a given tree decomposition of width tw. However, for nonlocal problems, like the fundamental class of connectivity problems, for a long time it was unknown how to do this faster than tw O(tw) The rank-based approach introduces a new technique to speed up dynamic programming algorithms which is likely to have more applications. The determinant-based approach use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
302
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(304 citation statements)
references
References 32 publications
1
302
0
1
Order By: Relevance
“…Each of the vertices t 5 and t 6 must be one of types f3, u3, f4, u4, f5, and a u5-vertex, and each of their weights decreases by at least m 3 = min{w 3 , Δ 3 , w 4 , Δ 4 , w 5 , Δ 5 }. Thus, the total weight decrease in the branch of delete(vt 1 ) is at least w 5 − w 4 + w 3 + 2m 3 .…”
Section: Branching On Edges Around F5-vertices (Branchingmentioning
confidence: 99%
See 3 more Smart Citations
“…Each of the vertices t 5 and t 6 must be one of types f3, u3, f4, u4, f5, and a u5-vertex, and each of their weights decreases by at least m 3 = min{w 3 , Δ 3 , w 4 , Δ 4 , w 5 , Δ 5 }. Thus, the total weight decrease in the branch of delete(vt 1 ) is at least w 5 − w 4 + w 3 + 2m 3 .…”
Section: Branching On Edges Around F5-vertices (Branchingmentioning
confidence: 99%
“…Hence, the weight of vertex v decreases by Δ 5,3 , and both weights of vertices t 1 and t 2 each decrease by w 3 . Thus, the total weight decrease in the branch of delete(vt 1 ) is at least w 5 − w 3 + 2w 3 .…”
Section: Fig 17mentioning
confidence: 99%
See 2 more Smart Citations
“…Saether and Telle address this problem in their paper [13] by introducing a new parameter, split-matching-width, which lies between treewidth and clique-width in terms of generality. They show that even though graphs of restricted split-matching-width might be dense, solving problems such as Hamiltonian Cycle can be done in FPT time.Recently, it was shown that Hamiltonian Cycle parameterized by treewidth is in EPT [1,6], meaning it can be solved in n O(1) 2 O(k) -time. In this paper, using tools from [6], we show that also parameterized by split-matching-width Hamiltonian Cycle is EPT.…”
mentioning
confidence: 99%